Seismic performance of a clutched inerter for structures with curved surface sliders. (March 2023) - Jangid, R.S.
Abstract: The performance of the clutched inerter in limiting the seismic response of structures isolated by curved surface slider (CSS) is investigated. The chosen structure is a flexible multi-floor building with an idealized linear shear-type behaviour. The equations governing the motion of an isolated structure with a clutched inerter under earthquake excitation have been derived. Initially, using the equivalent linearization technique, the isolated building's stationary floor absolute acceleration, isolator displacement, and device forces are evaluated. The stochastic earthquake excitation is considered to be a filtered white-noise Kanai-Tajimi model. The performance of the clutched inerter in mitigating the response of the isolated structure is studied by varying system parameters. The important parameters included are the inertance ratio of the clutched inerter, the period and friction coefficient of the CSS, and the flexibility of the superstructure. Further, there exists an optimum inertance of the clutched inerter for which the structure's highest floor absolute acceleration reaches its minimum level. The influence of important system parameters on the optimum inertance of the clutched inerter is also investigated. Finally, the performance of the clutched inerter as a supplemental device for the base-isolated structure is investigated when subjected to recorded earthquake motions consisting of near-fault as well as far-field types. The trends of results of isolated structures with clutched inerter under the recorded earthquake motions were in good agreement with that under stochastic excitation. It is demonstrated that the supplemental clutched inerter is effective in reducing the displacement response of base-isolated structures.